Derivational Affixes in Writing Analytical Exposition Text - Simaremare, Destriani; Silalahi, Dumaris E (JOLLT Journal of Languages and Language Teaching, 2021)
This research is about the analysis of derivational affixes in Writing Analytical Exposition Text. It intended to describe the process of derivational affixes and to find out the types, the structure, and the functions of each derivational affixes in writing analytical exposition text by the twelve grade students from YouTube. The qualitative method was used to investigate derivational affixes in writing analytical exposition text. The data were collected by documented study. They were collected from students’ results of making texts about analytical Exposition text, finding the text about analytical exposition, choosing the text that relevant with Corona virus disease, and the last searched the words that contain derivational affixes, the researcher identified. The results of this study showed that derivational affixes were found in writing analytical exposition text. There were three types of affix used. They were prefix, suffix, and circumfix. There was no infix used. Kinds of prefix found were pre-, dis-, re-, on-, under-, inter-, micro-, trans-, over-, al-, In-, out-. Kinds of suffix found were -ment, -ly, -ness, -ion, -y, -er, -ive, -ous, -ant, -ious, -ation, -en, -wards, -ition, -ed, -est, -ies, -ities -ily, -ence, -ing, -side. Kinds of circumfix found were Trans-ed, In-ation, inter-ion, dis-ed, re-ation, un-y, anti-ion, un–ed, in-ly, trans-ion, inter –ed, re-ing, trans-ing, in- ing, in-ent. The function of derivational affixes found in writing analytical exposition were verb formation, noun formation, adjective formation, and adverb formation, in which sometimes in the process of word formation, it did not always change the part of speech even though it had got the addition of affixes, such as noun into noun, verb into verb, and adjective into adjective. There were many derivational affixes. Moreover, suffix –ing to form a noun and –ly to form an adverb the most dominant affixes.